The ‘envers du décor’ of Suffragette Imagery: Anti-Suffrage Caricature - Abby Franchitti (Cahiers Victoriens et Edouardiens)
The visible historical discourse that surrounds ‘the woman question’, and more specifically speaking, the acquisition of the women’s right to vote, most frequently evokes the question from the Suffragette or the Suffragist point of view. Articles, books, photographs and exhibits centre on the unrelenting combat waged for sexual equality, the vote on the ‘same terms as men’. A recent exhibit has revealed the photos taken by the police of the Suffragettes in prison.Faced with Suffragette ‘publicity’, those opposed to ‘the Cause’ for women were forced to take a stand and create a movement against women’s suffrage. They launched a counter attack using numerous propaganda techniques. Among those were representations of the Suffragette and her goals, which they satirised by caricatures in their newspaper, The Anti-Suffrage Review, posters designed for their campaign and postcards.The specific aspect of the anti-suffrage campaign that I will examine in this paper is the use of caricature. Anxious to increase the support and the interest of its readership the Anti-Suffrage Review adopted this approach to criticize the Suffragettes and their tactics. In addition, they had posters and postcards designed to reinforce their campaign. However, the opposition to women’s suffrage was not confined to the organizations. Editors of popular postcards, quite in vogue at the time, also added their contribution to anti-suffrage propaganda. Indeed what could be funnier than to mock a man doing ‘woman’s work,’ while the wife and mother of the house was attending a political meeting? These are indeed the ‘envers du décor’ of the Suffragette imagery that could be found in newspapers and postcards printed in favour of ‘The Cause’.Before dealing with the campaigns’ caricatures, this paper will define the historical context: of the women’s movement and the formation of Suffragist and Suffragette (militant) organizations, and evoke the foundation of the Anti-Suffrage Leagues. This will be followed by the examination of the Anti-Suffragists’ utilization of caricature in contrast with Suffragette imagery.A study of this imagery enables the historian to analyze the values and convictions that were behind the anti-suffrage movement. They were those held dear not only by the eminent Victorians and Edwardians but by a majority of the average citizens as well.